Wildlife & warfare the life of James Stevenson-Hamilton - Carruthers, Jane (University of Natal Press, 2001)
James Stevenson-Hamilton can be credited with the creation of the Kruger National Park in South Africa. His wildlife accomplishments have been well documented, but the rest of his long and varied life has remained obscure, until now.
Includes bibliographical references (p. 223-233) and index
Keywords: Stevenson-Hamilton, James <1867-1957>; Stevenson-Hamilton, James -- 1867-1957; Geschichte; Game wardens -- South Africa -- Biography; Soldiers -- Great Britain -- Biography; Großbritannien; Südafrika (Staat); Kruger National Park (South Africa) -- History; Biografie